A kind of amino / phosphorus-grafted PPAN capsule and its preparation method and use
By grafting amine groups and phosphate groups onto polyacrylonitrile microspheres to prepare PPAN capsules, the problem of high cost of acidic uranium-containing wastewater treatment in the existing technology is solved, and efficient and economical uranium extraction and repeated use capabilities are achieved.
Patent Information
- Application Number
- CN202410919360.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-10
AI Technical Summary
In the prior art, when treating acidic uranium-containing wastewater, the liquid-liquid extraction method requires a large amount of reagents to generate secondary waste, resulting in high cost of treatment and waste disposal.
By grafting amine groups and phosphoric acid groups onto polyacrylonitrile microspheres, amine/phosphorus group-grafted PPAN capsules were prepared, taking advantage of their efficient adsorption of uranium under highly acidic conditions and their ability to be used repeatedly.
It has achieved high-efficiency extraction of uranium from highly acidic uranium-containing wastewater of 0
Smart Images

Figure CN118543342B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nuclear power, and in particular to an amine / phosphorus-grafted PPAN capsule. Background Art
[0002] With the rapid development of China's nuclear power industry, the demand for uranium is increasing. Before the seawater uranium extraction project is implemented, uranium ore can only be mined vigorously and efficiently to meet the demand for nuclear fuel uranium. At the front end of the nuclear fuel cycle, especially in the process of uranium mining, processing, extraction and concentration, a large amount of uranium-containing wastewater will be generated. In the process of nuclear fuel cycle, a large amount of acidic uranium wastewater will be generated. In the process of rare earth mining, a large amount of acidic uranium-containing wastewater will also be generated. For these acidic uranium-containing wastes, liquid-liquid extraction is currently mainly used to treat and recover uranium. The extraction separation method requires a large amount of reagents in the extraction, stripping and solution washing processes, and also produces secondary waste, which greatly increases the cost of the treatment process and waste disposal. Therefore, how to efficiently and deeply purify and extract uranium in highly acidic wastewater is a major problem that needs to be solved urgently in the nuclear fuel cycle system.
[0003] At present, the extraction and recovery of uranium under acidic conditions mainly focuses on some materials containing P=O, NH - , C=O functional group extractant. Therefore, in order to overcome the defects of liquid-liquid extraction, researchers have synthesized some organic adsorbents such as phosphonic acid, aminophosphoric acid and amine oxime compounds. Among them, primary amine, tertiary amine and amide modified materials have strong complexing ability for uranium, and phosphorus-containing compounds are the most commonly used extractants for uranium extraction and separation. Therefore, aminophosphoric acid can easily react with uranium due to the amino and phosphate groups contained in it, thereby extracting uranium. However, the reagents used in the main synthesis process are relatively expensive, and they are mainly fibrous adsorption materials, and the material cost is high. Summary of the invention
[0004] The purpose of the present invention is to provide an amino / phosphorus-grafted PPAN capsule and a preparation method and use thereof. The present invention is to graft an amino group and a phosphoric acid group onto a PAN microsphere to synthesize a PPAN capsule, so as to achieve efficient extraction of uranium from uranium-containing wastewater. Compared with the previous synthesis method, the synthesis method of the present invention is easy to operate, has a simple synthesis route, and has a low reaction cost. It can be produced in large quantities, provides a possible development path for future industrial production applications, and has important significance and potential application value for the sustainable development of nuclear resources.
[0005] In one aspect, the present invention provides a method for preparing amino / phosphorus-grafted PPAN capsules, the preparation method comprising the following steps:
[0006] Step 1) Synthesis of PAN microspheres by phase inversion method:
[0007] First, PAN powder and N,N-dimethylformamide solution were mixed at a mass ratio of 1:10-18, and stirred at 50-66°C for 1.5-2.5h to obtain a PAN polymer solution; the molecular weight of the PAN powder was Mw=8.5×10 4 , the particle size of the PAN powder is 20~50μm;
[0008] Then, a surfactant is dissolved in deionized water to obtain a non-solvent, the PAN polymer solution is extracted and squeezed into the non-solvent, and the non-solvent is continuously stirred during the squeezing process, and a PAN microsphere pre-product wrapped with the PAN polymer is obtained by reaction, and the PAN microsphere pre-product is washed and dried to obtain PAN microspheres; the surface of the PAN microspheres is smooth, and the particle size of the PAN microspheres is 0.8-1.2 mm;
[0009] Step 2) Amination of the PAN microspheres:
[0010] Weigh the PAN microspheres and put them into a flask, add triethylenetetramine and deionized water into the flask, and stir with a magnetic stirrer; then place the flask in an oil bath, condense and reflux, heat to 88-95° C. and react for 3.6-4.5 hours to obtain a preliminary APAN capsule; after the preliminary APAN capsule is cooled to room temperature, rinse the preliminary APAN capsule with deionized water at 65-70° C. until it is neutral, and dry to obtain an APAN capsule; the ratio of the PAN microspheres, triethylenetetramine and deionized water is 0.8-1.2 g: 40 mL: 20 mL;
[0011] Step 3) Phosphorylation of the APAN capsule:
[0012] The APAN capsule, phosphinic acid, formaldehyde and ethanol are mixed and stirred with a magnetic bar for 13-18 minutes. After condensation and reflux for 4-10 minutes under nitrogen conditions, the mixture is heated to 95-110° C. and reacted for 10-13 hours to obtain a preliminary PPAN capsule. After the preliminary PPAN capsule is cooled to room temperature, the preliminary PPAN capsule is rinsed with deionized water at 65-70° C. until it is neutral, and dried to obtain a PPAN capsule. The ratio of the APAN capsule, phosphinic acid, formaldehyde and ethanol is 0.3-0.8 g: 8-12 g: 10 mL: 20 mL.
[0013] The "non-solvent" mentioned in the present invention is a solvent that is insoluble in PAN polymer and is added to the solution to cause phase separation, thereby encapsulating the PAN polymer into capsules or co-precipitating into spheres. It is also called non-solvent induced phase separation (NIPS), and its process flow is to dissolve the polymer in the solvent to form a homogeneous solution, then slowly add an extractant that is more miscible with the solvent to extract the solvent, forming a two-phase structure with the polymer as the continuous phase and the solvent as the dispersed phase, and then remove the solvent to obtain a polymer with a certain pore structure.
[0014] Furthermore, in the preparation method of the present invention, in the step 2), the particle size of the APAN capsule is 1.2-1.5 mm, and the surface morphology of the APAN capsule is that tiny holes appear on the surface, and the size range of the tiny holes is 0.43-4.0 μm.
[0015] Furthermore, in the preparation method of the present invention, in the step 1), the concentration of the surfactant in the non-solvent is 0.0008 to 0.0015 wt %.
[0016] Furthermore, in the preparation method of the present invention, in the step 1), the surfactant is a non-ionic surfactant, and preferably polyether P123.
[0017] Furthermore, in the preparation method of the present invention, in the step 1), the mass ratio of the non-solvent to the PAN polymer solution is 4.5-6:1.
[0018] Furthermore, in the preparation method of the present invention, the drying temperature in step 1) to step 3) is 70-80° C., and the drying time is 2.5-3.5 h.
[0019] In another aspect, the present invention provides an amino / phosphorus-grafted PPAN capsule, wherein the PPAN capsule is a PPAN capsule prepared by any one of the above items; the chemical structure of the PPAN capsule is as follows:
[0020]
[0021] Among them, R is -CH2-H(OH)P=O.
[0022] Furthermore, the particle size of the PPAN capsules of the present invention is 1.2-1.5 mm, and the surface of the PPAN capsules has holes, and the size of the holes ranges from 0.74-12.3 μm.
[0023] In the present invention, the area of the pores on the surface of the PPAN capsule is larger than the fine pores on the surface of the APAN capsule.
[0024] In the present invention, a cyano group on the polyacrylonitrile microsphere breaks a bond to form a carbon-nitrogen double bond, the nitrogen atom connects to a hydrogen atom of the amine group in ethylenediamine, and the other part connects to the carbon atom to generate an aminated APAN capsule. After adding phosphinic acid and formaldehyde solution, a Mannich reaction occurs with the amine group on the APAN capsule to generate an alkylaminomethylphosphite PPAN capsule. The weak alkalinity of the amide hinders the proton binding of the skeleton and keeps the surface of the PPAN capsule negative at low pH, which is conducive to PPAN capturing uranyl cations from an acidic solution.
[0025] The PPAN capsule of the present invention has good repetitive practicability. After repeated use, the removal rate of uranium adsorbed for the fifth time can still reach 92.5%. If a large amount of highly acidic uranium-containing waste liquid is used, a dynamic adsorption method-large column experiment can be used to complete it.
[0026] In another aspect, the present invention provides a use of any of the above-mentioned amino / phosphorus-grafted PPAN capsules, wherein the PPAN capsules are used for extracting uranium from highly acidic uranium-containing wastewater with a pH of 0<pH<4.
[0027] In the present invention, when 0<pH<4, Cl - 、NO3 - and SO4 2- With UO2 2+ The complexing ability of P=O and UO2 is very poor. 2+ Therefore, under the highly acidic condition of 0<pH<4, the PPAN capsule of the present invention has a strong complexing ability. - 、NO3 - and SO4 2- Under the conditions of existence, the adsorption rate of uranium can reach more than 86%.
[0028] Specifically, as Cl - and NO3 - With the increase of concentration, the adsorption rate of PPAN capsules to U(VI) remained basically unchanged. This is because high concentration of Cl - and NO3 - The main form of uranium U(VI) in the solution is UO2 2+ , will not affect the adsorption process, but as SO4 2- With the increase of concentration, the adsorption rate of PPAN capsule to U(VI) decreased slightly. This is due to the high concentration of SO4 2- Complexation with uranyl ions to form UO2(SO4 2- ) -(2n-2)n , making free UO2 2+ The concentration of uranium decreased, resulting in a decrease in the amount of uranium adsorbed on the PPAN capsule.
[0029] Furthermore, in the use described in the present invention, the specific steps of the extraction method are as follows:
[0030] S1: placing the PPAN capsule in highly acidic uranium-containing wastewater at 0<pH<4, performing oscillation adsorption, and after reaching adsorption equilibrium, performing solid-liquid separation to obtain uranium-containing PPAN capsules;
[0031] S2: Desorbing the uranium-containing PPAN capsule with a 0.2M NH4HCO3 solution to obtain a desorption solution and a PPAN capsule, evaporating and decomposing the desorption solution to obtain pure uranium recovery; and continuously using the PPAN capsule for the next extraction of uranium from highly acidic uranium-containing wastewater with a pH value of 0<pH<4.
[0032] Compared with the prior art, the present invention has the following beneficial technical effects:
[0033] The PPAN capsule of the present invention can be used repeatedly in highly acidic uranium-containing wastewater with a pH of 0<4 after adsorbing uranium and then eluting it. After repeated use for 5 times, the removal rate of adsorbed uranium can reach 92.5%. - 、NO3 - and SO4 2- In the presence of acidic uranium-containing wastewater with a pH of 0≤pH≤3, the PPAN capsules of the present invention still have a high removal rate of uranium, reaching 86%; in addition, the PPAN capsules of the present invention have better stability in high ionic strength solutions.
[0034] In addition, when the PPAN capsule of the present invention is used to treat uranium-containing wastewater, the adsorption time is relatively short, and the reaction can reach adsorption equilibrium within 1 to 2 hours, which effectively reduces the treatment time and improves the process treatment efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The surface morphology of the APAN capsule of the present invention;
[0036] Figure 2 This is a surface morphology image of the invented APAN capsule micrograph;
[0037] Figure 3 is the surface morphology of the PPAN capsule of the present invention;
[0038] Figure 4 This is a surface morphology image of the PPAN capsule micrograph of the present invention. DETAILED DESCRIPTION
[0039] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described in detail with reference to the accompanying drawings. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the specific implementation methods, they shall be carried out according to the conventional conditions or the conditions recommended by the manufacturer.
[0040] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims. The terms used in the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.
[0041] The present invention is further described in detail below in conjunction with specific embodiments. Example 1
[0042] The present invention provides a method for preparing an amino / phosphorus-grafted PPAN capsule, the method comprising the following steps:
[0043] Step 1) Synthesis of PAN microspheres by phase inversion method:
[0044] First, PAN powder and N,N-dimethylformamide solution are mixed at a mass ratio of 1:10-18, and stirred at 50-66°C for 1.5-2.5h to obtain a PAN polymer solution; the molecular weight Mw of the PAN powder is 8.5×104, and the particle size of the PAN powder is 25-30µm;
[0045] Then, polyether P123 is dissolved in deionized water to obtain a non-solvent, the PAN polymer solution is extracted and squeezed into the non-solvent, and the non-solvent is continuously stirred during the squeezing process, and a primary PAN microsphere wrapped with a PAN polymer is obtained by reaction, and the primary PAN microsphere is washed and dried to obtain PAN microspheres; the surface of the PAN microsphere is smooth, and the particle size of the PAN microsphere is 0.8-1.2 mm; the concentration of polyether P123 in the non-solvent is 0.0008-0.0015wt%, and the mass ratio of the non-solvent to the PAN polymer solution is 4.5-6:1.
[0046] Step 2) Amination of the PAN microspheres:
[0047] The PAN microspheres are weighed and put into a flask, triethylenetetramine and deionized water are added into the flask, and magnetic stirring is performed; the flask is then placed in an oil bath, condensed and refluxed, heated to 88-95° C., and reacted for 3.6-4.5 hours to obtain a primary APAN capsule; after the primary APAN capsule is cooled to room temperature, the primary APAN capsule is rinsed with deionized water at 65-70° C. until it is neutral, and dried to obtain an APAN capsule; the ratio of the PAN microspheres, triethylenetetramine and deionized water is 0.8-1.2 g: 40 mL: 20 mL; the particle size of the APAN capsule is 1.2-1.5 mm, and the surface morphology of the APAN capsule is that small holes appear on the surface, and the size range of the small holes is 0.43-4.0 μm.
[0048] Step 3) Phosphorylation of the APAN capsule:
[0049] The APAN capsule, phosphinic acid, formaldehyde and ethanol are mixed and stirred with a magnetic bar for 13-18 minutes, condensed and refluxed under nitrogen for 4-10 minutes, and then heated to 95-110° C. for reaction for 10-13 hours to obtain a PPAN capsule product; after the PPAN capsule product is cooled to room temperature, the PPAN capsule product is rinsed with deionized water at 65-70° C. until it is neutral, and dried to obtain a PPAN capsule; Figure 1 and Figure 2 The ratio of the APAN capsule, phosphinic acid, formaldehyde and ethanol is 0.3-0.8 g: 8-12 g: 10 mL: 20 mL.
[0050] The drying temperature in step 1) to step 3) is 70-80° C., and the drying time is 2.5-3.5 hours. Example 2
[0051] The present invention provides an amino / phosphorus-grafted PPAN capsule, wherein the PPAN capsule is the PPAN capsule prepared in the above-mentioned Example 1; the chemical structure of the PPAN capsule is as follows:
[0052]
[0053] Wherein, R is -CH2-H(OH)P=O.
[0054] The particle size of the PPAN capsule is 1.2-1.5 mm, and the surface of the PPAN capsule has holes, such as Figure 3 and Figure 4 The area of the surface pores of the PPAN capsule is larger than the fine pores on the surface of the APAN capsule, and the size of the pores ranges from 0.74 to 12.3 μm. Example 3
[0055] The present invention provides a use of the amino / phosphorus-grafted PPAN capsules described in the above-mentioned embodiment 1 and embodiment 2, wherein the PPAN capsules are used for extracting uranium from highly acidic uranium-containing wastewater with a pH of 1.
[0056] The specific steps of the extraction method in this embodiment 3 are as follows:
[0057] S1: placing the PPAN capsule into the uranium-containing acid wastewater for oscillation adsorption, and after reaching adsorption equilibrium, performing solid-liquid separation to obtain the uranium-containing PPAN capsule;
[0058] S2: Desorb the uranium-containing PPAN capsule with a 0.2M NH4HCO3 solution to obtain a desorption solution and a PPAN capsule. The desorption solution is evaporated and decomposed to recover pure uranium. The PPAN capsule is continuously used for the next uranium-containing acid wastewater treatment.
[0059] After testing, the adsorption amount of uranium ions by PPAN capsule in Example 3 was q max =123.2 mg / g. Example 4
[0060] The only difference between Example 4 and Example 3 is that the PPAN capsule is used for extracting uranium from highly acidic uranium-containing wastewater with a pH of 2.
[0061] After testing, the adsorption amount of uranium ions by PPAN capsule in Example 4 was q max =125.3 mg / g. Example 5
[0062] The only difference between Example 5 and Example 3 is that the PPAN capsule is used for extracting uranium from highly acidic uranium-containing wastewater with a pH of 2.5.
[0063] After testing, the adsorption amount of uranium ions by PPAN capsule in Example 5 was q max =124.5 mg / g. Example 6
[0064] The present invention provides a method for preparing an amino / phosphorus-grafted PPAN capsule, the method comprising the following steps:
[0065] Step 1) Synthesis of PAN microspheres by phase inversion method:
[0066] First, PAN powder and N,N-dimethylformamide solution are mixed at a mass ratio of 1:10-18, and stirred at 50-66° C. for 1.5-2.5 hours to obtain a PAN polymer solution; the molecular weight Mw of the PAN powder is 8.5×104;
[0067] Then, polyether P123 is dissolved in deionized water to obtain a non-solvent, the PAN polymer solution is extracted and squeezed into the non-solvent, and the non-solvent is continuously stirred during the squeezing process, and the PAN microspheres wrapped with the PAN polymer are obtained by reaction. After the PAN microspheres are filtered, they are first washed with anhydrous ethanol for 3 times, then washed with boiling water for 3 times, and finally dried at 70-80° C. for 2.5-3.5 hours to obtain PAN microspheres;
[0068] The surface of the PAN microspheres is smooth, and the particle size of the PAN microspheres is 0.8-1.2 mm; the concentration of the polyether P123 in the non-solvent is 0.001 wt %, and the mass ratio of the non-solvent to the PAN polymer solution is 5:1.
[0069] Step 2) Amination of the PAN microspheres:
[0070] The PAN microspheres are weighed and put into a flask, triethylenetetramine and deionized water are added into the flask, and magnetic stirring is performed; the flask is then placed in an oil bath, condensed and refluxed, heated to 88-95° C. for reaction for 3.6-4.5 hours, and a primary APAN capsule is obtained; after the primary APAN capsule is cooled to room temperature, the primary APAN capsule is rinsed with deionized water at 65-70° C. until it is neutral, and dried to obtain APAN capsules; the ratio of the PAN microspheres, triethylenetetramine and deionized water is 1 g: 40 mL: 20 mL; the particle size of the APAN capsule is 1.2-1.5 mm, and the surface morphology of the APAN capsule is that small holes appear on the surface.
[0071] Step 3) Phosphorylation of the APAN capsule:
[0072] The APAN capsule, phosphinic acid, formaldehyde and ethanol are mixed and stirred with a magnetic bar for 15 minutes. After condensation and reflux for 5 minutes under nitrogen conditions, the mixture is heated to 100° C. and reacted for 12 hours to obtain a preliminary PPAN capsule. After the preliminary PPAN capsule is cooled to room temperature, the preliminary PPAN capsule is rinsed with deionized water at 65-70° C. until it is neutral, and dried to obtain a PPAN capsule. The ratio of the APAN capsule, phosphinic acid, formaldehyde and ethanol is 0.5 g: 10 g: 10 mL: 20 mL.
[0073] The drying temperature in step 1) to step 3) is 70-80° C., and the drying time is 2.5-3.5 hours.
[0074] The PPAN capsules prepared in Example 6 were used to extract uranium from uranium-containing wastewater with a pH of 1 using the method of Example 3. The PPAN capsules were used repeatedly, and the uranium adsorption rate could still reach 92.5% on the fifth use.
[0075] The calculation method of the uranium removal rate of the PPAN capsule in the above Examples 1 to 6 is as follows: the concentrations of uranium ions in the uranium-containing wastewater before and after adsorption by the PPAN capsule are measured, namely, C0 and C, and the uranium removal rate is calculated according to the formula: uranium removal rate = (C0-C) / C0╳100%.
[0076] In the above Example 6, after the fourth adsorption of uranium on the PPAN capsule, 0.2 mol / L NH4HCO3 solution was used for desorption, and then the fifth adsorption of uranium was carried out. The concentrations of uranium ions in the uranium-containing wastewater before and after the fifth adsorption were measured, and the uranium removal rate of the fifth time was calculated as (C0-C5) / C0╳100%.
[0077] Through experimental testing, the PPAN capsules in Examples 1 to 4 above were - 、NO 3- and SO4 2- Under the condition of the presence of uranium and the uranium waste liquid with a pH of 0 < 4, the removal rate of uranium is still very high, reaching up to 86%, and the PPAN capsule has better stability in the high ionic strength solution; when the PPAN capsules in Examples 1 to 6 treat the uranium waste liquid, the reaction can reach adsorption equilibrium within 1 to 2 hours, and the adsorption time is short; after the PPAN capsules in Examples 1 to 6 adsorb uranium, they can be repeatedly used after elution, and the uranium adsorption for the fifth time can still reach 92.5%.
[0078] Comparative Example 1:
[0079] The difference between the preparation method of the amino / phosphorus-grafted PPAN capsules in this comparative example 1 and that in Example 6 is that the PAN powder in step 1) is replaced with PAN fibers, and finally the PPAN fiber capsules that are not completely and uniformly coated are obtained.
[0080] The PPAN fiber capsule of Comparative Example 1 was used to extract uranium from highly acidic uranium-containing waste liquid with a pH of 0<pH<4 by the method of Example 3. The PPAN fiber capsule was unstable and could not achieve the adsorption effect and could not be used repeatedly.
[0081] Comparative Example 2:
[0082] In this comparative example 2, TOPO-XAD-16 in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 1.
[0083] The specific extraction steps are as follows:
[0084] S1: Put the adsorbent TOPO-XAD-16 into the acid wastewater containing uranium, conduct oscillation adsorption, and after reaching adsorption equilibrium, perform solid-liquid separation to obtain the uranium-containing adsorbent TOPO-XAD-16. After testing, the adsorbent TOPO-XAD-16 has an adsorption capacity of uranium ions qmax =37.59 mg / g.
[0085] Comparative Example 3:
[0086] In this comparative example 3, the adsorbent CCOF-SCUI in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 1.
[0087] The specific extraction steps are as follows:
[0088] S1: Place the adsorbent CCOF-SCUI into the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, perform solid-liquid separation to obtain the uranium-containing adsorbent CCOF-SCUI.
[0089] The adsorption capacity of uranium ions by adsorbent CCOF-SCUI was q max =50mg / g.
[0090] Comparative Example 4:
[0091] In this comparative example 4, the adsorbent DPTS Ion-Imprinted SBA-15 in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 1.
[0092] The specific extraction steps are as follows:
[0093] S1: Put the adsorbent DPTS Ion-Imprinted SBA-15 into the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, perform solid-liquid separation to obtain the uranium-containing adsorbent DPTS Ion-Imprinted SBA-15.
[0094] The adsorption capacity of uranium ions by adsorbent DPTS Ion-Imprinted SBA-15 was q max =60 mg / g.
[0095] Comparative Example 5:
[0096] This comparative example 5 uses the adsorbent [NH4][COF-SO3 - ] / SPES is used for the extraction of uranium from highly acidic uranium-containing wastewater with pH=1.
[0097] The specific extraction steps are as follows:
[0098] S1: Adsorbent [NH4][COF–SO3 - ] / SPES was placed in the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, solid-liquid separation was performed to obtain the uranium-containing adsorbent [NH4][COF–SO3 - ] / SPES.
[0099] After testing, the adsorbent [NH4][COF–SO3 - ] / The adsorption amount of uranium ions by SPES max =94.2 mg / g.
[0100] Comparative Example 6:
[0101] In this comparative example 6, the adsorbent MA-U-PA in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 1.
[0102] The specific extraction steps are as follows:
[0103] S1: Putting the adsorbent MA-U-PA into the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, solid-liquid separation is performed to obtain the uranium-containing adsorbent MA-U-PA.
[0104] The adsorption capacity of uranium ions by adsorbent MA-U-PA was q max =106.7 mg / g.
[0105] Comparative Example 7:
[0106] In this comparative example 7, the adsorbent Sulfonated GO in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 2.
[0107] The specific extraction steps are as follows:
[0108] S1: Put the adsorbent Sulfonated GO into the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, perform solid-liquid separation to obtain the uranium-containing adsorbent Sulfonated GO.
[0109] The adsorption capacity of uranium ions by the adsorbent Sulfonated GO was q max =45.05 mg / g.
[0110] Comparative Example 8:
[0111] In this comparative example 8, the adsorbent PEI-GO in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 2.
[0112] The specific extraction steps are as follows:
[0113] S1: Put the adsorbent PEI-GO into the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, perform solid-liquid separation to obtain the uranium-containing adsorbent PEI-GO.
[0114] The adsorption capacity of uranium ions by adsorbent PEI-GO was q max=48 mg / g.
[0115] Comparative Example 9:
[0116] In this comparative example 9, the adsorbent Zn(L)(HBTC) in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 2.
[0117] The specific extraction steps are as follows:
[0118] S1: placing the adsorbent Zn(L)(HBTC) into the uranium-containing acid wastewater for oscillation adsorption, and after reaching adsorption equilibrium, performing solid-liquid separation to obtain the uranium-containing adsorbent Zn(L)(HBTC).
[0119] The adsorption capacity of uranium ions by adsorbent Zn(L)(HBTC) was q max =92 mg / g.
[0120] Comparative Example 10:
[0121] In this comparative example 10, the adsorbent UiO-68(Zr)-P(O)(OH)2 in the prior art is used to extract uranium from highly acidic uranium-containing wastewater with a pH of 2.5.
[0122] The specific extraction steps are as follows:
[0123] S1: Place the adsorbent UiO-68(Zr)-P(O)(OH)2 into the uranium-containing acid wastewater for oscillation adsorption. After reaching adsorption equilibrium, perform solid-liquid separation to obtain the uranium-containing adsorbent UiO-68(Zr)-P(O)(OH)2.
[0124] The adsorption capacity of uranium ions by adsorbent UiO-68(Zr)-P(O)(OH)2 was q max =37.59 mg / g.
[0125] From the comparison of the adsorption effect of the adsorbents of Examples 3 to 5 and Comparative Examples 2 to 10 on uranium ions, it can be seen that the adsorption effect of the PPAN capsules of the present invention on uranium ions in uranium-containing acid wastewater is much better than that of the adsorbents in the prior art, and the removal rate of uranium ions in highly acidic uranium-containing acid wastewater by PPAN capsules is still very high after repeated use.
[0126] The present invention is described by the above specific embodiments, and those skilled in the art should understand that various changes and equivalent substitutions can be made to the present invention without departing from the scope of the present invention. The parts not described in detail in the present specification are well-known technologies to those skilled in the art. In addition, various modifications can be made to the present invention for specific situations or specific circumstances without departing from the scope of the present use. Therefore, the present invention is not limited to the specific embodiments disclosed, but should include all implementation methods falling within the scope of the claims of the present invention.
Claims
1. A method for preparing amino / phosphorus-grafted PPAN capsules for extracting uranium from highly acidic uranium-containing wastewater with a pH of 0 < 4, characterized in that: The chemical structural formula of the PPAN capsule is as follows: , wherein R is -CH2-H(OH)P=O; The preparation method comprises the following steps: Step 1) Synthesis of PAN microspheres by phase inversion method: First, PAN powder and N,N-dimethylformamide solution were mixed at a mass ratio of 1:10-18, and stirred at 50-66°C for 1.5-2.5h to obtain a PAN polymer solution; the molecular weight of the PAN powder was Mw=8.5×10 4 , the particle size of the PAN powder is 20~50μm; Then, a surfactant is dissolved in deionized water to obtain a non-solvent, the PAN polymer solution is extracted and squeezed into the non-solvent, and the non-solvent is continuously stirred during the squeezing process, and a preliminary PAN microsphere product wrapped with the PAN polymer is obtained by reaction, and the preliminary PAN microsphere product is washed and dried to obtain PAN microspheres; The surface of the PAN microspheres is smooth, and the particle size of the PAN microspheres is 0.8-1.2 mm; Step 2) Amination of the PAN microspheres: Weigh the PAN microspheres and put them into a flask, add triethylenetetramine and deionized water into the flask, and stir with a magnetic stirrer; then place the flask in an oil bath, condense and reflux, heat to 88-95° C. and react for 3.6-4.5 hours to obtain a preliminary APAN capsule; after the preliminary APAN capsule is cooled to room temperature, rinse the preliminary APAN capsule with deionized water at 65-70° C. until it is neutral, and dry to obtain an APAN capsule; The ratio of PAN microspheres, triethylenetetramine and deionized water is 0.8-1.2 g: 40 mL: 20 mL; Step 3) Phosphorylation of the APAN capsule: The APAN capsule, phosphinic acid, formaldehyde and ethanol are mixed and stirred with a magnetic bar for 13 to 18 minutes, condensed and refluxed under nitrogen for 4 to 10 minutes, and then heated to 95 to 110° C. for reaction for 10 to 13 hours to obtain a PPAN capsule product; after the PPAN capsule product is cooled to room temperature, the PPAN capsule product is rinsed with deionized water at 65 to 70° C. until it is neutral, and dried to obtain a PPAN capsule; The ratio of the APAN capsule, phosphinic acid, formaldehyde and ethanol is 0.3-0.8 g: 8-12 g: 10 mL: 20 mL; The particle size of the PPAN capsule is 1.2-1.5 mm, and the surface of the PPAN capsule has holes, and the size of the holes ranges from 0.74 to 12.3 μm.
2. The preparation method according to claim 1, characterized in that In the step 2), the particle size of the APAN capsule is 1.2-1.5 mm, and the surface morphology of the APAN capsule is that tiny holes appear on the surface, and the size range of the tiny holes is 0.43-4.0 μm.
3. The preparation method according to claim 2, characterized in that In the step 1), the concentration of the surfactant in the non-solvent is 0.0008-0.0015 wt %.
4. The preparation method according to claim 3, characterized in that: In the step 1), the surfactant is a non-ionic surfactant.
5. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of the non-solvent to the PAN polymer solution is 4.5-6:
1.
6. The preparation method according to claim 1, characterized in that: The drying temperature in step 1) to step 3) is 70-80° C., and the drying time is 2.5-3.5 hours.
7. Use of amino / phosphorus-grafted PPAN capsules prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The PPAN capsule is used for extracting uranium from highly acidic uranium-containing wastewater with a pH of 0<pH<4.
8. The use according to claim 7, characterized in that The specific steps of the extraction method are as follows: S1: placing the PPAN capsule in highly acidic uranium-containing wastewater at 0<pH<4, performing oscillation adsorption, and after reaching adsorption equilibrium, performing solid-liquid separation to obtain uranium-containing PPAN capsules; S2: Desorbing the uranium-containing PPAN capsule with a 0.2M NH4HCO3 solution to obtain a desorption solution and a PPAN capsule, evaporating and decomposing the desorption solution to obtain pure uranium and recovering it; the PPAN capsule is continuously used for the next extraction of uranium from highly acidic uranium-containing wastewater with a pH value of 0<pH<4.
Citation Information
Patent Citations
Multifunctional spherical chelating adsorbent preparation method though microwave radiation
CN104368321A
Corn husk adsorbent material modified by hypophosphorous acid, preparation method and application thereof
CN108854979A
Preparation method of amido / phosphorus-based grafted functional fiber and efficient extraction of uranium by using amido / phosphorus-based grafted functional fiber
CN114797794A